Sub-0.2 V impact ionization in Si n-i-p-i-n diode - Das, Bhaskar; Sushama, Sushama; Schulze, Jörg; Ganguly, Udayan (IEEE Transactions on Electron Devices, 2016)
Sub-0.6 V experimental demonstration of impact ionization (II) is a challenge in Si devices. We propose a new n+-i-δ-p+-i-n+ diode structure where II current is integrated as stored charge, which strongly affects the output current. The device was fabricated and measured current-voltage was compared with 'ideal' TCAD-based drift diffusion simulations to evaluate the excess over the barrier current due to impact ionization. Based on this study, impact ionization at 0.2-0.5 V over three orders of current is observed for the first time at room temperature (300 K) in Si. The temperature dependence of impact ionization observed is consistent with experimental and theoretical expectations from literature. Such low voltage impact ionization sustained over three orders of current at RT enables the feasibility of advanced computational devices.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Impact ionization (II); low bias; Si-diode